Perbedaan Hasil Belajar Siswa antara Media Circuit Pintar dan PowerPoint Ditinjau dari Kemampuan Berpikir Kritis - Bintang Gilang Laksmana; Subuh Isnur Haryudo; Meini Sondang Sumbawati; Rina Harimurti (BRILIANT: Jurnal Riset dan Konseptual, 2026)
This study aimed to analyze the differences in students’ learning outcomes between the use of Circuit Pintar and PowerPoint learning media in terms of critical thinking skills in the subject of Basic Electrical Engineering at SMKN 3 Surabaya. This study employed a quantitative approach with a 2×2 factorial design. The sample consisted of 72 students divided into experimental and control classes. Data were analyzed using Two-Way ANOVA to determine the effect of learning media, critical thinking skills, and the interaction between both variables on students’ learning outcomes. The results showed that there was no significant difference in students’ critical thinking skills between the use of Circuit Pintar and PowerPoint media with a significance value of 0.165 > 0.05. In addition, there was no significant difference in learning outcomes between the two-learning media with a significance value of 0.082 > 0.05. The analysis also revealed no significant interaction between learning media and critical thinking skills on students’ learning outcomes with a significance value of 0.176 > 0.05. However, Circuit Pintar consistently demonstrated descriptive advantages and has the potential to become an effective website-based learning media alternative in vocational electrical engineering education.